Three-dimensional microcrystalline glass, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202410123198.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-30
AI Technical Summary
[0003]但传统3D微晶玻璃在应用于盖板领域时,会存在光学性能变差的问题,且传统3D微晶玻璃在热弯晶化过程中会发生比较大的体积变化,进而导致3D微晶玻璃的翘曲较高
[0031]本申请提供的三维微晶玻璃,从内部化学组分的角度出发,对各化学组分进行合理配伍,使得到的三维微晶玻璃兼备翘曲值小和光学性能优异的优点,进而能够避免抛光处理所导致的微晶玻璃强度降低;进一步地,本申请提供的三维微晶玻璃在各化学组分的协同下,使其具有较高的硬度。
Smart Images

Figure CN117945651B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of glass, specifically to a three-dimensional microcrystalline glass, its preparation method, and its application. Background Technology
[0002] Cover glass has evolved from 2D to 2.5D to 3D (three-dimensional). Compared with traditional 2.5D glass, ceramic cover glass and metal backplate, 3D glass can be combined with flexible OLED screens and has the advantages of being drop-resistant, wear-resistant, transparent and clean, fingerprint-resistant, anti-glare and weather-resistant. Therefore, it has been widely used as screen cover for 3C products such as smartphones, smartwatches, tablets, dashboards and other wearable products.
[0003] However, when traditional 3D glass-ceramics are used in cover glass applications, their optical performance deteriorates. Furthermore, traditional 3D glass-ceramics undergo significant volume changes during hot bending and crystallization, leading to substantial warpage. Currently, the main approach to addressing warpage in 3D glass-ceramics is a "contaminate first, then treat" method, such as single-sided polishing to repair deformation. While this method can reduce warpage, polishing also reduces the strength of the glass-ceramics. Summary of the Invention
[0004] Based on this, this application provides a three-dimensional glass-ceramic, its preparation method, and its application. The three-dimensional glass-ceramic provided by this application has excellent optical properties, and this application, starting from the perspective of the internal composition of the three-dimensional glass-ceramic, enables the obtaining of a three-dimensional glass-ceramic with a small warpage value, thereby effectively avoiding the reduction in strength of the glass-ceramic caused by polishing.
[0005] A first aspect of this application provides a three-dimensional microcrystalline glass comprising, by mass percentage, the following chemical components: SiO2 65%~75%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 0.5%~5%, ZrO2 0.5%~7%, Na2O 0%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0%~1%, TiO2 0%~2%, and Sb2O3 0%~1%;
[0006] The three-dimensional microcrystalline glass comprises lithium disilicate and lithium feldspar crystal phases, with a mass ratio of lithium feldspar to lithium disilicate of (0.8~0.95):1; the total mass percentage of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2 and Sb2O3 is 1%~13%.
[0007] In one embodiment, the mass percentage of the lithium disilicate crystalline phase in the three-dimensional microcrystalline glass is 35% to 45%.
[0008] In one embodiment, the mass percentage of the lithium feldspar phase in the three-dimensional microcrystalline glass is 28% to 42%.
[0009] In one embodiment, the sum of the mass percentages of the lithium disilicate phase and the lithium feldspar phase in the three-dimensional glass-ceramic is 63% to 87%.
[0010] In one embodiment, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 65%~73%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 2%~4.5%, ZrO2 0.5%~7%, Na2O 0.5%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0.2%~1%, TiO2 0.1%~2%, and Sb2O3 0.2%~1%.
[0011] A second aspect of this application provides a method for preparing the three-dimensional glass-ceramic described in any embodiment of the first aspect of this application, comprising the following steps:
[0012] Take sub-crystallized glass, wherein the chemical composition of the sub-crystallized glass is the same as that of the three-dimensional microcrystalline glass described in any embodiment of the first aspect of this application;
[0013] The subcrystalline glass is hot-bent to form the three-dimensional microcrystalline glass.
[0014] The hot bending forming process includes preheating, forming, and cooling processes performed sequentially.
[0015] In one embodiment, the preheating process includes sequentially performed staged heating preheating and heat preservation processes, wherein the temperature of the heat preservation process is 740°C to 800°C; before reaching the temperature of the heat preservation process, the staged heating preheating process includes n temperature gradients, where n is a positive integer greater than or equal to 5.
[0016] In one embodiment, the staged preheating includes five temperature gradients, wherein the staged preheating includes a first preheating, a second preheating, a third preheating, a fourth preheating, and a fifth preheating performed sequentially. The temperature of the first preheating is 380℃~420℃, the temperature of the second preheating is 530℃~570℃, the temperature of the third preheating is 580℃~620℃, the temperature of the fourth preheating is 630℃~670℃, and the temperature of the fifth preheating is 700℃~740℃.
[0017] In one embodiment, the molding process includes m molding process segments, where m is 3, 4, or 5;
[0018] The temperature difference between the first molding process section and the heat preservation treatment temperature is -5℃ to 5℃.
[0019] In one embodiment, m is 4, and the molding process includes a first molding process segment, a second molding process segment, a third molding process segment, and a fourth molding process segment performed sequentially.
[0020] The molding process parameters include: performing the first molding process segment at 735℃~805℃ and 0.02MPa~0.2MPa, increasing the pressure to 0.04MPa~0.4MPa for the second molding process segment, continuing to increase the pressure to 0.06MPa~0.6MPa for the third molding process segment, increasing the pressure to 0.08MPa~0.8MPa for the third molding process segment, and cooling to 630℃~670℃ and increasing the pressure to 0.1MPa~1MPa for the fourth molding process segment.
[0021] In one embodiment, the cooling process includes p cooling process segments, where p is 1, 2, or 3.
[0022] In one embodiment, p is 3, and the cooling process includes a first cooling process segment, a second cooling process segment, and a third cooling process segment performed sequentially; the temperature of the first cooling process segment is 480℃~520℃, the temperature of the second cooling process segment is 330℃~370℃, and the temperature of the third cooling process segment is room temperature.
[0023] In one embodiment, the subcrystalline glass comprises, by mass percentage, the following chemical components: 65%~75% SiO2, 5%~11% Al2O3, 7%~15% Li2O, 0.1%~1% B2O3, 0.5%~5% P2O5, 0.5%~7% ZrO2, 0%~5% Na2O, 0%~1% K2O, 0%~1% MgO, 0%~1% CaO, 0%~1% BaO, 0%~1% ZnO, 0%~2% TiO2, and 0%~1% Sb2O3; wherein the sum of the mass percentages of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2, and Sb2O3 is 1%~13%.
[0024] In one embodiment, the subcrystalline glass comprises lithium metasilicate, lithium disilicate, and lepidolite phases; the total mass percentage of lithium metasilicate, lithium disilicate, and lepidolite phases in the subcrystalline glass is 20% to 30%.
[0025] In one embodiment, the mass percentage ratio of the lithium feldspar phase, lithium disilicate phase, and lithium metasilicate phase in the subcrystalline glass is (0.82~1.15):1:(1.4~4).
[0026] In one embodiment, the preparation steps of the subcrystalline glass include:
[0027] Take a substrate glass and heat it to 530℃~650℃ at a heating rate of 5℃ / min~12℃ / min for 3h~8h for nucleation treatment; then heat it to 600℃~750℃ at a heating rate of 0.5℃ / min~8℃ / min for crystallization treatment, and cool it to room temperature to prepare the subcrystallized microcrystalline glass.
[0028] In one embodiment, the preparation steps of the substrate glass include:
[0029] According to the chemical composition of the three-dimensional microcrystalline glass, a molten liquid is prepared at 1450℃~1600℃; after the molten liquid is shaped, the matrix glass is prepared.
[0030] A third aspect of this application provides an application of the three-dimensional microcrystalline glass described in any embodiment of the first aspect of this application in the field of cover plate materials.
[0031] The three-dimensional microcrystalline glass provided in this application, from the perspective of internal chemical composition, rationally combines various chemical components to obtain a three-dimensional microcrystalline glass that has the advantages of low warpage value and excellent optical performance, thereby avoiding the reduction in strength of microcrystalline glass caused by polishing treatment; furthermore, the three-dimensional microcrystalline glass provided in this application has high hardness due to the synergy of various chemical components. Attached Figure Description
[0032] Figure 1 A process flow diagram of the method for preparing three-dimensional glass-ceramics provided in this application;
[0033] Figure 2 This is a temperature change curve diagram from step S20 of this application;
[0034] Figure 3 This is a temperature change curve diagram from step S30 of this application;
[0035] Figure 4 This is a structural diagram of the simple hot bending device used in the embodiments of this application. Detailed Implementation
[0036] The following detailed description, in conjunction with specific embodiments, provides a more complete and clear account of the three-dimensional glass-ceramic of this application, its preparation method, and its applications. This application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0038] In this article, "one or more" refers to any one, two or more of the listed items.
[0039] In this application, terms such as "first aspect," "second aspect," "third aspect," "fourth aspect," and "fifth aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," "fourth," and "fifth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0040] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0041] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0042] Unless otherwise specified, the percentage content mentioned in this application refers to mass percentage for solid-liquid mixtures and solid-phase-solid mixtures, and volume percentage for liquid-phase-liquid mixtures.
[0043] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.
[0044] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.
[0045] A first aspect of this application provides a three-dimensional microcrystalline glass comprising, by mass percentage, the following chemical components: SiO2 65%~75%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 0.5%~5%, ZrO2 0.5%~7%, Na2O 0%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0%~1%, TiO2 0%~2%, and Sb2O3 0%~1%;
[0046] The three-dimensional microcrystalline glass comprises lithium disilicate and lithium feldspar crystal phases, with a mass ratio of lithium feldspar to lithium disilicate of (0.8~0.95):1; the total mass percentage of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2 and Sb2O3 is 1%~13%.
[0047] SiO2 is an essential component of three-dimensional glass-ceramics, serving as a forming oxide that constitutes the glass network. It forms the main structure of the glass-ceramic and is also a major component of the crystalline phase. In this application, to ensure the uniformity of crystal precipitation, the mass percentage of SiO2 is limited to 65% to 75%. Understandably, the mass percentage of SiO2 can be selected from any value between 65% and 75%. Specifically, the mass percentage of SiO2 includes, but is not limited to, 66%, 68%, 69%, 69.5%, 70%, 70.5%, 71%, 72%, or 74%.
[0048] Al₂O₃ is an important component of the crystalline phase of lithium feldspar, belonging to the network intermediate oxides. Simultaneously, Al₂O₃ is also a major component controlling the crystalline phase ratio and grain size. In this application, to control the crystalline phase ratio and grain size, the mass percentage of Al₂O₃ is limited to 5% to 11%. It is understood that the mass percentage of Al₂O₃ can be selected from any value between 5% and 11%. Specifically, the mass percentage of Al₂O₃ includes, but is not limited to, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, or 10%.
[0049] Li₂O is a network-external oxide in glass formation, providing free oxygen and disrupting the glass's network structure, thereby improving its viscosity. Simultaneously, Li₂O is a permeate oxide (LiAlSi₄O₃). 10 The necessary chemical components for crystal phase formation. In this application, to balance the crystallization stability of the glass, the mass percentage of Li2O is limited to 7% to 15%. Specifically, the mass percentage of Li2O includes, but is not limited to, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 12%, 13%, or 15%.
[0050] B2O3 can be used as a flux to reduce the high-temperature viscosity of glass. However, excessive B2O3 can reduce the phase separation of the glass, leading to a decrease in glass transparency. Therefore, this application limits the mass percentage of B2O3 to 0.1% to 1%. Specifically, the mass percentage of B2O3 includes, but is not limited to, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.85%, or 0.9%.
[0051] P2O5 is an essential component as an auxiliary nucleating agent. To ensure the crystallization effect and transparency of the glass, this application limits the mass percentage of P2O5 to 0.5% to 5%. Specifically, the mass percentage of P2O5 includes, but is not limited to, 1%, 1.5%, 1.8%, 1.9%, 2%, 2.2%, 2.5%, 3%, or 4%.
[0052] ZrO2 acts as a nucleating agent, reducing grain size. However, excessively high ZrO2 content can lead to the formation of large amounts of white precipitates, negatively impacting the transparency of the glass-ceramic. Specifically, the mass percentage of ZrO2 in this application includes, but is not limited to, 1%, 1.5%, 2%, 2.5%, 2.8%, 2.9%, 3%, 4%, 4.5%, 5%, 5.5%, 5.6%, or 6%.
[0053] Na₂O, being a network exooxide, can significantly reduce the viscosity of the base glass, promoting the melting and clarification of glass-ceramics. However, an increase in Na₂O content leads to a decrease in the chemical durability of the glass, and the increase in the glass phase in the glass-ceramic makes it more difficult to control glass crystallization. Therefore, in this application, the mass percentage of Na₂O is set to 0%~5%. Specifically, the mass percentage of Na₂O includes, but is not limited to, 0.5%, 0.55%, 0.6%, 0.8%, 0.9%, 0.95%, 1%, 1.5%, 2%, 3%, 3.1%, 3.2%, 3.5%, or 4%.
[0054] Like Na2O, K2O is a component that lowers the melting temperature of glass. The mass percentage of K2O includes, but is not limited to, 0.1%, 0.5%, 0.55%, 0.58%, 0.6%, 0.8%, 0.85%, or 0.9%.
[0055] MgO, CaO, BaO, and ZnO are all components that improve the melt flowability of glass-ceramics. The mass percentage of MgO includes, but is not limited to, 0.1%, 0.4%, 0.45%, 0.5%, 0.55%, 0.58%, 0.6%, 0.8%, 0.85%, or 0.9%. The mass percentage of CaO includes, but is not limited to, 0.1%, 0.4%, 0.45%, 0.5%, 0.55%, 0.58%, 0.6%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%. The mass percentage of BaO includes, but is not limited to, 0.1%, 0.4%, 0.45%, 0.5%, 0.55%, 0.58%, 0.6%, 0.65%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%. The mass percentage of ZnO includes, but is not limited to, 0.1%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.58%, 0.6%, 0.65%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%.
[0056] TiO2 and Sb2O3 have high refractive indices, which can improve the optical properties of glass-ceramics, as well as their hardness and strength. However, excessive TiO2 and Sb2O3 may increase the melting temperature of the glass-ceramics. Specifically, in this application, the mass percentage of TiO2 is set to 0%~2%. Specifically, the mass percentage of TiO2 includes, but is not limited to, 0.1%, 0.13%, 0.15%, 0.18%, 0.2%, 0.45%, 0.5%, 0.52%, 0.55%, 0.6%, 0.8%, 0.9%, 1%, 1.05%, 1.1%, 1.4%, 1.5%, 1.55%, 1.6%, 1.8%, or 2%. The mass percentage of Sb2O3 includes, but is not limited to, 0.1%, 0.18%, 0.2%, 0.23%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.58%, 0.6%, 0.65%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%.
[0057] Furthermore, to balance the hardness and melting temperature of the glass-ceramic, this application specifies that the total mass percentage of optional components Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2, and Sb2O3 is 1% to 13%. It is understood that the total mass percentage of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2, and Sb2O3 includes, but is not limited to, 1.5%, 2%, 2.1%, 2.2%, 2.3%, 2.5%, 3%, 5%, 5.1%, 5.2%, 5.3%, 5.5%, 6%, 6.5%, 6.8%, 6.9%, 6.95%, 7%, 7.5%, 7.8%, 7.9%, 8%, 9%, 10%, or 12%.
[0058] This application defines a three-dimensional glass-ceramic comprising a lithium disilicate crystalline phase and a lithium feldspar crystalline phase. The lithium disilicate crystalline phase has a high refractive index and optical transparency; its presence can adjust the refractive index of the glass-ceramic, making it more flexible and controllable in optical applications. The lithium feldspar crystalline phase has high hardness and compressive strength, which can enhance the mechanical strength and durability of the glass-ceramic. Controlling the mass ratio of the lithium feldspar crystalline phase to the lithium disilicate crystalline phase to be (0.8~0.95):1 can enhance the synergy between the two crystalline phases, ensuring that the glass-ceramic has excellent optical properties and hardness, while also possessing a low warpage value. Specifically, the mass percentage ratio of the lithium feldspar crystalline phase to the lithium disilicate crystalline phase (0.8~0.95):1 includes, but is not limited to, 0.8:1, 0.81:1, 0.85:1, 0.9:1, 0.91:1, 0.92:1, 0.93:1, 0.94:1, or 0.95:1.
[0059] In one example, the mass percentage of the lithium disilicate crystalline phase is 35% to 45%. It is understood that the mass percentage of the lithium disilicate crystalline phase includes, but is not limited to, 35.8%, 36%, 36.5%, 37%, 38%, 40%, 41%, 41.5%, 42%, 44%, 44.5%, or 45%.
[0060] In one example, the mass percentage of the lepidolite phase is 28% to 42%. Understandably, the mass percentage of the lepidolite phase includes, but is not limited to, 29%, 33%, 33.5%, 34%, 35%, 36%, 36.5%, 38%, 38.5%, 40%, 40.5%, 41%, or 42%.
[0061] In one example, the sum of the mass percentages of the lithium disilicate crystalline phase and the petalite crystalline phase is 63% to 87%. Specifically, the sum of the mass percentages of the lithium disilicate crystalline phase and the petalite crystalline phase includes, but is not limited to, 65%, 65.5%, 66%, 68%, 69%, 70%, 74%, 74.5%, 75%, 79%, 79.5%, 80%, 84%, 85%, 86%, or 87%.
[0062] Preferably, the three-dimensional microcrystalline glass comprises the following chemical components by mass percentage: SiO2 65%~73%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 2%~4.5%, ZrO2 0.5%~7%, Na2O 0.5%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0.2%~1%, TiO2 0.1%~2%, and Sb2O3 0.2%~1%.
[0063] In one example, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 69.5%~69.8%, Al2O3 6%~6.2%, Li2O 10.1%~10.2%, B2O3 0.4%~5%, P2O5 2.4%~2.5%, ZrO2 4.2%~4.3%, Na2O 1.4%~1.6%, K2O 0.8%~0.85%, MgO 0.4%~0.45%, CaO 0.8%~0.9%, BaO 0.9%~1.1%, ZnO 0.85%~0.95%, TiO2 1.05%~1.1%, and Sb2O3 0.35%~0.45%.
[0064] In one example, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 70.55%~70.65%, Al2O3 8%~8.05%, Li2O 8.35%~8.45%, B2O3 0.82%~0.84%, P2O5 2.43%~2.48%, ZrO2 1.8%~1.85%, Na2O 3.15%~3.5%, K2O 0%~0.05%, MgO 0.9%~1.1%, CaO 0%~0.1%, BaO 0.85%~0.9%, ZnO 0.2%~0.25%, TiO2 1.55%~1.6%, and Sb2O3 0.9%~1.1%.
[0065] In one example, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 70.65%~70.7%, Al2O3 7.05%~7.15%, Li2O 10%~12%, B2O3 0.65%~0.75%, P2O5 2.15%~2.2%, ZrO2 6.1%~6.15%, Na2O 0.5%~0.55%, K2O 0%~0.05%, MgO 0%~0.05%, CaO 0.95%~1%, BaO 0%~0.05%, ZnO 0.35%~0.4%, TiO2 0.1%~0.2%, and Sb2O3 0.15%~0.25%.
[0066] In one example, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 73.5%~73.6%, Al2O3 6.6%~6.8%, Li2O 9.45%~9.5%, B2O3 0.5%~0.7%, P2O5 4.6%~4.8%, ZrO2 2.9%~2.95%, Na2O 0%~0.05%, K2O 0.5%~0.55%, MgO 0%~0.05%, CaO 0.05%~0.15%, BaO 0.5%~0.6%, ZnO 0%~0.05%, TiO2 0%~0.05%, and Sb2O3 0.85%~0.95%.
[0067] In one example, the three-dimensional glass-ceramic comprises, by mass percentage, the following chemical components: SiO2 69.05%~69.1%, Al2O3 8.85%~8.95%, Li2O 9.2%~9.3%, B2O3 0.15%~0.25%, P2O5 1.8%~1.9%, ZrO2 5.5%~5.55%, Na2O 0.9%~0.95%, K2O 0.55%~0.6%, MgO 0.55%~0.6%, CaO 0.4%~0.5%, BaO 0.6%~0.7%, ZnO 0.9%~0.95%, TiO2 0.45%~0.55%, and Sb2O3 0.55%~0.65%.
[0068] Currently, the most common forming method for 3D glass is 3D hot bending. The principle behind 3D hot bending is that glass, when heated to near its softening point, can change shape under external force. The hot bending process for mobile phone cover glass mainly includes three stages: preheating and softening, hot pressing and forming, and cooling and shaping. Ideally, the entire hot bending process involves approximately 20 workstations or more. First, the finely sculpted glass is placed in a graphite mold, then the mold is placed in a hot bending machine. In the preheating stage, the glass is heated to specific temperatures to soften it. In the forming stage, pressure is applied to gradually bring the softened glass into contact with the mold. Finally, in the cooling stage, the glass is gradually cooled and shaped to obtain 3D microcrystalline glass.
[0069] Compared to the conventional 3D hot bending process for glass, the fabrication process of 3D microcrystalline glass is more complex. Currently, its main fabrication routes include:
[0070] (1) First 3D hot bending, then crystallization: First, the flat glass is hot bent to form 3D curved glass, and then the 3D curved glass is microcrystallized to obtain 3D curved microcrystalline glass. However, the 3D glass produced by this method is prone to deformation during the crystallization process, and the process requirements are high and the production cost is high.
[0071] (2) Crystallize first, then 3D hot bend: The fully crystalline microcrystalline glass is hot bent into shape, which has higher mechanical strength and hardness, resulting in a low yield of mechanical processing before hot bending. Moreover, the softening temperature of fully crystalline microcrystalline glass is higher, which increases the processing difficulty of the 3D hot bending machine and the production cost is high.
[0072] Based on this, in a second aspect, this application provides a method for preparing three-dimensional microcrystalline glass as described in any example of the first aspect of this application. The preparation method provided by this application performs crystallization simultaneously during the hot bending process, so that the sub-crystallized glass reaches the expected degree of crystallinity, which can effectively reduce the energy consumption of the hot bending machine and make the warping of the three-dimensional microcrystalline glass after hot bending less, making it suitable for the field of mobile phone cover glass.
[0073] Specifically, please refer to Figure 1 The method for preparing the three-dimensional glass-ceramic includes the following steps:
[0074] S10. Prepare a molten liquid according to the chemical composition of the three-dimensional microcrystalline glass at 1450℃~1600℃; after molding the molten liquid, prepare the matrix glass.
[0075] S20. Take a substrate glass and heat it to 530℃~650℃ at a heating rate of 5℃ / min~12℃ / min for 3~8h for nucleation treatment; heat it to 600℃~750℃ at a heating rate of 0.5℃ / min~8℃ / min for crystallization treatment, and cool it to room temperature to prepare the subcrystallized microcrystalline glass.
[0076] S30. Take sub-crystallized glass and perform hot bending forming process on the sub-crystallized glass to prepare the three-dimensional microcrystalline glass. The hot bending forming process includes the sequential steps of S301 preheating treatment, S302 forming treatment, and S303 cooling treatment.
[0077] The method for preparing three-dimensional glass-ceramics provided in this application includes sequential nucleation, crystallization, and hot bending processes. By limiting the process parameters during nucleation and crystallization, the crystalline phase composition of the subcrystalline glass-ceramics can be reasonably controlled, making it easier for lithium metasilicate and lithium disilicate crystalline phases to organize and nucleate. Simultaneously, Li₂O, Al₂O₃, and SiO₂ in the matrix glass further form lithiofeldspar crystals under certain conditions. At this point, the crystallinity of the crystalline phases in the subcrystalline glass is 20%~30%, making it easy to perform hot bending in a hot bending mold, and achieving simultaneous hot bending and crystallization of the glass. That is, after hot bending, both "three-dimensional shaping" and "crystallization reaching the expected crystallinity" are achieved simultaneously, resulting in a high-performance three-dimensional glass-ceramics. Specifically, in step S20, the temperature change for preparing the subcrystalline glass-ceramics is as follows: Figure 2 As shown, in step S30, the temperature change during the preparation of the three-dimensional glass-ceramic is as follows: Figure 3 As shown.
[0078] In one example, in step S20, the crystal phase of the subcrystallized glass includes lithium metasilicate, lithium disilicate, and lithium feldspar crystal phases.
[0079] Specifically, the mass percentage of lithium metasilicate phase in the subcrystalline glass is 11.5% to 15%. The lithium metasilicate phase can be transformed into lepidolite and lithium disilicate phases during the subsequent hot bending process. Simultaneously, Li₂O, Al₂O₃, and SiO₂ in the subcrystalline glass also transform into lepidolite phases during the hot bending process, thereby enhancing the hardness of the three-dimensional glass-ceramic. Specifically, the mass percentage of lithium metasilicate phase in the subcrystalline glass includes, but is not limited to, 11.9%, 12%, 12.2%, 12.3%, 12.5%, 12.8%, 12.9%, 13%, 14%, 14.5%, 14.8%, or 14.9%.
[0080] Specifically, the mass percentage of lithium disilicate phase in the subcrystalline glass is 3.5% to 8.3%. Understandably, the mass percentage of lithium disilicate phase in the subcrystalline glass includes, but is not limited to, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 5%, 5.3%, 5.4%, 5.45%, 5.5%, 5.6%, 7%, 7.2%, 7.3%, 7.4%, 8%, 8.1%, 8.2%, or 8.3%.
[0081] Specifically, the mass percentage of the lithium feldspar crystalline phase in the subcrystalline glass is 3.3% to 7.1%. Understandably, the mass percentage of the lithium feldspar crystalline phase in the subcrystalline glass includes, but is not limited to, 3.35%, 3.4%, 3.45%, 4%, 4.4%, 4.5%, 4.6%, 6%, 6.1%, 6.2%, 6.3%, 6.35%, 6.4%, 7%, 7.05%, or 7.1%. Preferably, the mass percentage of the lithium feldspar crystalline phase in the subcrystalline glass is 6.1% to 7.1%.
[0082] Specifically, the total mass percentage of lithium metasilicate, lithium disilicate, and lepidolite phases in the subcrystalline glass is 20% to 30%. The total mass percentage of these phases in the subcrystalline glass includes, but is not limited to, 22%, 22.5%, 23%, 24%, 25%, 26%, 27%, 28%, or 30%.
[0083] Preferably, in step S20, the mass percentage ratio of the lithium feldspar phase, lithium disilicate phase, and lithium metasilicate phase in the subcrystalline glass is (0.82~1.15):1:(1.4~4). Limiting the mass percentages of the lithium metasilicate phase, lithium disilicate phase, and lithium feldspar phase in the subcrystalline glass to this range allows the crystallized glass to be suitable for subsequent hot bending forming processes, ensuring that the prepared three-dimensional microcrystalline glass has a low warpage value, excellent optical properties, and high hardness. Specifically, the mass percentage ratios of the lithium feldspar phase, lithium disilicate phase, and lithium metasilicate phase in the subcrystalline glass include, but are not limited to, 0.82:1:2.3, 0.85:1:2.4, 0.85:1:1.5, 0.86:1:1.4, 0.86:1:1.5, 0.86:1:1.6, 0.87:1:1.7, 0.89:1:3.9, 0.89:1:4, 0.9:1:4, 1.14:1:2.25, and 1.15:1:2.3.
[0084] In one example, in step S20, the subcrystalline glass comprises the following chemical components by mass percentage: SiO2 65%~75%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 0.5%~5%, ZrO2 0.5%~7%, Na2O 0%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0%~1%, TiO2 0%~2%, and Sb2O3 0%~1%; wherein the sum of the mass percentages of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2, and Sb2O3 is 1%~13%. Understandably, the chemical composition of subcrystalline glass and substrate glass is the same as that of three-dimensional microcrystalline glass. Therefore, the specific chemical composition of subcrystalline glass and substrate glass will not be described in detail here.
[0085] In one example, in step S301, the preheating process includes sequentially performing staged heating preheating and heat preservation processes, wherein the temperature of the heat preservation process is 740℃~800℃; before reaching the temperature of the heat preservation process, the staged heating preheating includes n temperature gradients, where n is a positive integer greater than or equal to 5.
[0086] In one example, the staged preheating includes five temperature gradients, wherein the staged preheating comprises a first preheating, a second preheating, a third preheating, a fourth preheating, and a fifth preheating performed sequentially. The first preheating temperature is 380℃~420℃, the second preheating temperature is 530℃~570℃, the third preheating temperature is 580℃~620℃, the fourth preheating temperature is 630℃~670℃, and the fifth preheating temperature is 700℃~740℃. It is understood that the first preheating temperature includes, but is not limited to, 380℃, 390℃, 400℃, 410℃, or 420℃. The second preheating temperature includes, but is not limited to, 540℃, 550℃, 560℃, or 570℃. The third preheating temperature includes, but is not limited to, 580℃, 590℃, 600℃, 610℃, or 620℃. The fourth preheating temperature includes, but is not limited to, 640℃, 650℃, 660℃, or 670℃. The fifth preheating temperature includes, but is not limited to, 710°C, 720°C, 730°C, or 740°C. Understandably, the pressure during the preheating process is atmospheric pressure. Furthermore, the times for the first, second, third, fourth, and fifth preheating processes are each independently selected from 50s to 150s.
[0087] Specifically, the temperature for heat preservation treatment includes, but is not limited to, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, or 800℃. Preferably, the heat preservation treatment time is 100s to 300s.
[0088] In one example, in step S302, the molding process includes m molding process segments, where m is 3, 4, or 5; wherein the temperature difference between the first molding process segment and the temperature of the heat preservation process is -5℃ to 5℃. Setting the temperature difference between the first molding process segment and the heat preservation process within the range of -5℃ to 5℃ ensures that the microcrystalline glass is heated uniformly during the molding process, thus better maintaining its shape stability. Preferably, the temperature of the first molding process segment is the same as the temperature of the heat preservation process.
[0089] In one example, m is 4, and the molding process includes a first molding process segment, a second molding process segment, a third molding process segment, and a fourth molding process segment performed sequentially.
[0090] The molding process parameters include: performing the first molding process segment at 735℃~805℃ and 0.02MPa~0.2MPa, increasing the pressure to 0.04MPa~0.4MPa for the second molding process segment, continuing to increase the pressure to 0.06MPa~0.6MPa for the third molding process segment, increasing the pressure to 0.08MPa~0.8MPa for the third molding process segment, and cooling to 630℃~670℃ and increasing the pressure to 0.1MPa~1MPa for the fourth molding process segment.
[0091] In one example, in step S303, the cooling process includes p cooling process segments, where p is 1, 2, or 3.
[0092] In one example, p is 3, and the cooling process includes a first cooling process segment, a second cooling process segment, and a third cooling process segment performed sequentially; the temperature of the first cooling process segment is 480℃~520℃, the temperature of the second cooling process segment is 330℃~370℃, and the temperature of the third cooling process segment is room temperature. Understandably, in this application, the time for each of the first and second cooling process segments is independently selected from 50s to 150s. The third cooling process segment cools the temperature from the second cooling process segment to room temperature.
[0093] A third aspect of this application provides an application of the three-dimensional microcrystalline glass described in any example of the first aspect of this application in the field of cover plate materials.
[0094] The following specific embodiments further illustrate this application, but this application is not limited to the following embodiments.
[0095] Example 1
[0096] Embodiment 1 of this application provides a three-dimensional microcrystalline glass and its preparation method, including the following steps:
[0097] (1) Prepare the batch according to the chemical composition shown in Table 1, put it into a three-dimensional mixer and mix it evenly to make a batch; pour the batch into a platinum crucible and place it in a high-temperature furnace to prepare a molten liquid at 1450℃~1600℃; after the molten liquid is formed, prepare the base glass.
[0098] (2) The substrate glass was placed in a crystallization furnace and heated from room temperature to 550°C at a heating rate of 9°C / min, and held for 7 hours for nucleation treatment; then heated to 625°C at a heating rate of 3°C / min for crystallization treatment, and cooled to room temperature to prepare sub-crystallized microcrystalline glass; the chemical composition and crystal phase composition of the sub-crystallized microcrystalline glass are shown in Table 1.
[0099] (3) The subcrystalline glass is wire cut, ground and polished and CNC machined to make a 0.5mm~1mm thick subcrystalline microcrystalline glass transparent sheet.
[0100] (4) A simple hot bending device is built inside the annealing furnace using refractory materials. Figure 4 The subcrystalline glass pieces were placed in the apparatus and heated to the forming temperature of 760℃. The heat-bending properties of the subcrystalline microcrystalline glass were then observed.
[0101] (5) After the subcrystalline microcrystalline glass is hot-bent, it is placed into a graphite mold and then placed in a 3D hot bending machine for preheating, forming and cooling treatments in sequence. The preheating treatment includes sequential staged preheating and heat preservation treatment, with the heat preservation treatment temperature being 740°C. Before reaching the heat preservation treatment temperature, the staged preheating includes five temperature gradients: the first preheating temperature is 400°C, the second preheating temperature is 550°C, the third preheating temperature is 600°C, the fourth preheating temperature is 650°C, and the fifth preheating temperature is 720°C, with each preheating time being 90s. Then, the temperature is raised to 740°C and heat preservation treatment is performed for 180s.
[0102] (6) After the preheating treatment is completed, the molding process is carried out. The molding process includes the first molding process segment, the second molding process segment, the third molding process segment and the fourth molding process segment in sequence. The temperature of the first molding process segment is 740℃ and the pressure applied by the mold is 0.05MPa; the temperature of the second molding process segment is 740℃ and the pressure applied by the mold is 0.08MPa; the temperature of the third molding process segment is 740℃ and the pressure applied by the mold is 0.1MPa; the temperature of the fourth molding process segment is 650℃ and the pressure applied by the mold is 0.1MPa; the dwell time of each molding process segment is 90s.
[0103] (7) Finally, the cooling process is carried out, which includes the first, second and third cooling processes in sequence. The temperature of the first cooling process is 500°C, the temperature of the second cooling process is 350°C, and the dwell time of each cooling process is 90s. Then, the third cooling process is carried out to cool from 350°C to 20°C to prepare 3D microcrystalline glass. The corresponding preparation parameters and crystal phase composition of 3D microcrystalline glass are shown in Table 1.
[0104] Test methods
[0105] Crystal phase and crystal phase content: Based on X-ray diffraction (XRD), the crystal phase and its corresponding mass percentage were determined using Rietveld analysis. Grain size: The grain size of the glass was measured using a FEI Quanta scanning electron microscope (SEM). Warpage value: The warpage value was measured using a laser testing instrument. Transmittance: Measured using a Perkin Elmer Lambda 950 UV-Vis spectrophotometer, according to GB / T 40415 standard. Haze: The haze of the sample was measured using a SUGA Optics HZ-V3 haze meter, according to GB / T 2410 standard. Hardness: The hardness of the glass surface was measured using an Innolux FALCON 400 hardness tester, according to GB / T 4340 standard.
[0106] Examples 2 to 5
[0107] Examples 2 through 5 are basically the same as Example 1, the main difference being that the chemical composition, crystal phase, and hot bending process parameters of the 3D microcrystalline glass are different from those in Example 1. The specific parameters for Examples 2 through 5 are shown in Table 1.
[0108] Table 1
[0109]
[0110] (Continued from Table 1)
[0111]
[0112] As shown in Table 1, by defining the chemical composition and crystal phase composition of the 3D microcrystalline glass and using the 3D hot bending process described in this application, the resulting 3D microcrystalline glass exhibits a low warpage value (0.065 mm~0.076 mm), high transmittance (90.2%~91.6%), low haze (0.14~0.23), and high hardness (726.4 kgf / mm²). 2 ~760.3 kgf / mm 2 ).
[0113] Comparative Example 1
[0114] (1) Prepare the batch according to the chemical composition shown in Table 2, put it into a three-dimensional mixer and mix it evenly to make a batch; pour the batch into a platinum crucible and place it in a high-temperature furnace to prepare a molten liquid at 1450℃~1600℃; after the molten liquid is formed, prepare the base glass.
[0115] (2) The substrate glass was placed in a crystallization furnace and heated from room temperature to 530°C at a heating rate of 9°C / min, and held for 4 hours for nucleation treatment; then heated to 600°C at a heating rate of 3°C / min for crystallization treatment, and cooled to room temperature to prepare subcrystallized microcrystalline glass; the chemical composition and crystal phase composition of the subcrystallized microcrystalline glass are shown in Table 2.
[0116] (3) The subcrystalline glass is wire cut, ground and polished and CNC machined to make a 0.5mm~1mm thick subcrystalline microcrystalline glass transparent sheet.
[0117] (4) A simple hot bending device is built inside the annealing furnace using refractory materials. Figure 4 The subcrystalline glass pieces were placed in the apparatus and heated to the forming temperature of 720℃. The heat-bending properties of the subcrystalline microcrystalline glass were then observed.
[0118] Comparative Examples 2 to 10
[0119] Comparative Examples 2 through 10 are basically the same as Comparative Example 1, with the main difference being that the chemical composition, crystal phase, and nucleation crystallization process parameters of the subcrystalline glass are different from those in Example 1. The specific parameters for Comparative Examples 2 through 10 are shown in Table 2.
[0120] Table 2
[0121]
[0122] Table 3
[0123]
[0124] As shown in Tables 2 and 3, Comparative Examples 1 and 10 do not contain any of the three crystalline phases. In Comparative Examples 2 and 4 through 9, the mass percentage ratios of the lithium feldspar, lithium disilicate, and lithium metasilicate phases in the subcrystalline glass are not within the range of (0.82~1.15):1:(1.4~4), making them unsuitable for hot bending processes and unable to form the crystalline phases of the three-dimensional microcrystalline glass of this application. In Comparative Example 3, the mass percentage of Al2O3 is not within the range of 5%~11% of this application, and it does not meet the chemical composition requirements of the three-dimensional microcrystalline glass of this application.
[0125] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0126] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection appended to this application. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. A three-dimensional microcrystalline glass, characterized in that, By mass percentage, it includes the following chemical components: SiO2 65%~75%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 0.5%~5%, ZrO2 0.5%~7%, Na2O 0%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0%~1%, TiO2 0%~2%, and Sb2O3 0.2%~1%; The three-dimensional microcrystalline glass comprises lithium disilicate and lithium feldspar phases, with a mass ratio of lithium feldspar to lithium disilicate phase of (0.8~0.95):1; the total mass percentage of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2 and Sb2O3 is 1%~13%. The preparation steps of the three-dimensional microcrystalline glass include: taking sub-crystallized glass, wherein the chemical composition of the sub-crystallized glass is the same as that of the three-dimensional microcrystalline glass; subjecting the sub-crystallized glass to hot bending forming to prepare the three-dimensional microcrystalline glass; the hot bending forming process includes preheating treatment, forming treatment and cooling treatment performed sequentially. The subcrystalline glass comprises lithium metasilicate, lithium disilicate, and lepidolite phases; the total mass percentage of lithium metasilicate, lithium disilicate, and lepidolite phases in the subcrystalline glass is 20% to 30%; the mass percentage ratio of lepidolite, lithium disilicate, and lithium metasilicate phases in the subcrystalline glass is (0.82 to 1.15): 1: (1.4 to 4).
2. The three-dimensional microcrystalline glass according to claim 1, characterized in that, The three-dimensional glass-ceramic has one or more of the following characteristics: (1) In the three-dimensional glass-ceramic, the mass percentage of the lithium disilicate crystalline phase is 35%~45%; (2) In the three-dimensional glass-ceramic, the mass percentage of the transparent lithium feldspar crystal phase is 28%~42%; (3) In the three-dimensional microcrystalline glass, the sum of the mass percentages of the lithium disilicate crystal phase and the lithium feldspar crystal phase is 63%~87%.
3. The three-dimensional microcrystalline glass according to claim 1 or 2, characterized in that, By mass percentage, it includes the following chemical components: SiO2 65%~73%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 2%~4.5%, ZrO2 0.5%~7%, Na2O 0.5%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0.2%~1%, TiO2 0.1%~2%, and Sb2O3 0.2%~1%.
4. A method for preparing a three-dimensional microcrystalline glass according to any one of claims 1 to 3, characterized in that, Includes the following steps: Take subcrystallized glass, wherein the chemical composition of the subcrystallized glass is the same as that of the three-dimensional microcrystalline glass according to any one of claims 1 to 3; The subcrystalline glass is hot-bent to form the three-dimensional microcrystalline glass. The hot bending forming process includes a preheating process, a forming process, and a cooling process performed sequentially. The subcrystalline glass comprises lithium metasilicate, lithium disilicate, and lepidolite phases; the total mass percentage of lithium metasilicate, lithium disilicate, and lepidolite phases in the subcrystalline glass is 20% to 30%. The mass percentage ratio of the lithium feldspar phase, lithium disilicate phase, and lithium metasilicate phase in the subcrystalline glass is (0.82~1.15):1:(1.4~4).
5. The method for preparing three-dimensional glass-ceramics according to claim 4, characterized in that, The preheating process includes sequential staged heating preheating and heat preservation treatment, wherein the temperature of the heat preservation treatment is 740℃~800℃; before reaching the temperature of the heat preservation treatment, the staged heating preheating includes n temperature gradients, where n is a positive integer greater than or equal to 5.
6. The method for preparing three-dimensional glass-ceramics according to claim 5, characterized in that, The phased preheating includes five temperature gradients. The staged preheating includes a first preheating, a second preheating, a third preheating, a fourth preheating, and a fifth preheating, performed sequentially. The temperature of the first preheating is 380℃~420℃, the temperature of the second preheating is 530℃~570℃, the temperature of the third preheating is 580℃~620℃, the temperature of the fourth preheating is 630℃~670℃, and the temperature of the fifth preheating is 700℃~740℃.
7. The method for preparing three-dimensional glass-ceramics according to claim 5 or 6, characterized in that, The molding process includes m molding process segments, where m is 3, 4 or 5; The temperature difference between the first molding process section and the heat preservation treatment temperature is -5℃ to 5℃.
8. The method for preparing three-dimensional glass-ceramics according to claim 7, characterized in that, m is 4, and the molding process includes a first molding process segment, a second molding process segment, a third molding process segment, and a fourth molding process segment performed sequentially; The process parameters for the molding process include: the temperature of the first molding process segment is 740℃, and the pressure applied by the mold is 0.05MPa; the temperature of the second molding process segment is 740℃, and the pressure applied by the mold is 0.08MPa; the temperature of the third molding process segment is 740℃, and the pressure applied by the mold is 0.1MPa; the temperature of the fourth molding process segment is 650℃, and the pressure applied by the mold is 0.1MPa; the dwell time of each molding process segment is 90s.
9. The method for preparing three-dimensional glass-ceramics according to claim 4, characterized in that, The cooling process includes p cooling process segments, where p is 1, 2, or 3.
10. The method for preparing three-dimensional glass-ceramics according to claim 9, characterized in that, p is 3, and the cooling process includes a first cooling process segment, a second cooling process segment, and a third cooling process segment performed sequentially; the temperature of the first cooling process segment is 480℃~520℃, the temperature of the second cooling process segment is 330℃~370℃, and the temperature of the third cooling process segment is room temperature.
11. The method for preparing three-dimensional glass-ceramics according to any one of claims 4 to 6, characterized in that, The subcrystalline glass comprises the following chemical components by mass percentage: SiO2 65%~75%, Al2O3 5%~11%, Li2O 7%~15%, B2O3 0.1%~1%, P2O5 0.5%~5%, ZrO2 0.5%~7%, Na2O 0%~5%, K2O 0%~1%, MgO 0%~1%, CaO 0%~1%, BaO 0%~1%, ZnO 0%~1%, TiO2 0%~2%, and Sb2O3 0%~1%; wherein the total mass percentage of Na2O, K2O, MgO, CaO, BaO, ZnO, TiO2, and Sb2O3 is 1%~13%.
12. The method for preparing three-dimensional glass-ceramics according to claim 11, characterized in that, The preparation steps of the subcrystalline glass include: Take a substrate glass and heat it to 530℃~650℃ at a heating rate of 5℃ / min~12℃ / min for 3h~8h for nucleation treatment; then heat it to 600℃~750℃ at a heating rate of 0.5℃ / min~8℃ / min for crystallization treatment, and cool it to room temperature to prepare the subcrystallized glass.
Citation Information
Patent Citations
Three-dimensional microcrystalline glass and preparation method thereof
CN113248152A
High-transmittance low-haze glass composition, microcrystalline glass and preparation method thereof
CN115772002A